Reflective Writing on an ESL Writing Course - Anna Wärnsby; Asko Kauppinen; Damian Finnegan (Educare)
Research shows that student reflective writing is a valuable window into student learning, particularly student metacognition; however, our knowledge of the challenges of accessing metacognition to inform curriculum design and assessment practices in the ESL (English as a Second Language) context is less robust. This paper reports two qualitative studies of student reflective writing on an ESL writing course within a teacher education programme. The studies investigate how student metacognition manifests itself in reflective papers and how mapping student metacognition can inform evidence-based curriculum design and assessment. The data comes from several iterations of an ESL writing course and is analysed using directed and conventional content analyses. Our results expose a complex relation between metacognition, curriculum design and assessment practices: 1) unless scaffolded by the curriculum design to use precise terminology, students resort to expressing their understanding of the course content in terms of everyday, vernacular language and 2) student reflective writing not only provides a more nuanced picture of their learning than the final course grades but is invaluable for developing scaffolding and assessment practices. Based on our results, we recommend integrating structured reflection as part of the regular curricula to gauge ESL student metacognition and monitor more precisely their uptake of course content.